Enhancing supply chain transparency in manufacturing companies: Impact on stakeholder engagement - Kylkisalo, Anniina (My University, 2026)
Supply chain transparency has become a key issue in manufacturing industry as sustainability requirements, regulations, and stakeholder pressure have increased. It remains unclear how transparency efforts affect stakeholder trust and engagement, even though companies have tried to improve supply chain transparency through various monitoring and reporting practices. The aim of this study is to examine transparency in manufacturing companies’ supply chains and its impact on stakeholders. The study is based on a literature review and analyzes the existing academic research on supply chain transparency and stakeholder engagement. The data was analyzed using a thematic analysis to identify key themes and find appropriate answers to the research questions. The results of this study emphasize that supply chain transparency is particularly influenced by regulatory and stakeholder pressures, technological enablers for transparency, and the complexity of global and multi-tiered supply chains. Transparency can also strengthen stakeholder commitment and trust, especially when it is perceived as authentic and credible. The study also highlights challenges such as limited visibility of suppliers at lower levels of the supply chains and the risk of symbolic transparency.

Toimitusketjujen läpinäkyvyys on noussut keskeiseksi teemaksi teollisuudessa kestävyyteen liittyvien vaatimusten, sääntelyn sekä sidosryhmäpaineiden lisääntyessä. On edelleen epäselvää, miten läpinäkyvyyspyrkimykset vaikuttavat sidosryhmien luottamukseen ja sitoutumiseen, vaikka yritykset ovat pyrkineet parantamaan toimitusketjujen läpinäkyvyyttä erilaisten seuranta- ja raportointikäytäntöjen avulla. Tämän tutkimuksen tavoitteena on tarkastella läpinäkyvyyttä teollisuuden toimitusketjuissa sekä sen vaikutusta sidosryhmiin. Tutkimus perustuu kirjallisuuskatsaukseen, ja siinä analysoidaan olemassa olevia akateemisia tutkimuksia toimitusketjujen läpinäkyvyydestä sekä sidosryhmävuorovaikutuksesta. Aineisto analysoitiin temaattisen analyysin avulla, jotta tunnistetaan keskeisiä teemoja sekä, että tutkimuskysymyksiin löydetään sopivat vastaukset. Tutkimuksen tuloksissa korostuu, että toimitusketjujen läpinäkyvyyteen vaikuttavat erityisesti sääntely- sekä sidosryhmäpaineet, teknologiset mahdollisuudet sekä globaalien ja monitasoisten toimitusketjujen monimutkaisuus. Läpinäkyvyys voi lisäksi vahvistaa sidosryhmien sitoutumista sekä luottamusta, erityisesti kun se koetaan aidoksi sekä uskottavaksi. Tutkimus tuo esiin myös haasteita, kuten rajallinen näkyvyys toimittajiin alemmalla tasolla sekä riski muodollisesta läpinäkyvyydestä.
Keywords: supply chains; transparency; manufacturing industry; stakeholder groups; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; fi=Tuotantotalouden ja tietojärjestelmätieteen kandidaattiohjelma|en=Bachelor’s Programme in Industrial Management and Information Systems|; Tuotantotalous